Relevance of Islamic Education Values in Malay Pantun - Suhernawati Suhernawati; Jarir Jarir; Rini Nopita; Betti Fariati (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Malay pantun, as an oral cultural heritage, carries noble values that transcend generations. This study aims to analyze the relevance of Islamic educational values embedded in Malay pantun within the context of contemporary society. It explores how these values can serve as a moral compass in shaping individual and societal character. Methodology: This research employs a qualitative descriptive approach with textual analysis to examine selected Malay pantun. The data were obtained through literature review and document analysis, focusing on identifying Islamic values such as honesty, patience, tolerance, and compassion within the pantun texts. Main Findings: The analysis reveals that Malay pantun contains fundamental Islamic educational values that remain relevant despite the evolving socio-cultural landscape. These values continue to play a significant role in character formation, fostering moral awareness and strengthening social harmony. Additionally, Malay pantun serves as an effective medium for da'wah, as its poetic and rhythmic nature enhances the reception of religious and ethical teachings. Novelty/Originality of this study: This study highlights the untapped potential of Malay pantun as a tool for cultural preservation and Islamic education in modern contexts. It provides new insights into how traditional oral literature can be adapted to contemporary educational frameworks, ensuring that Islamic teachings remain accessible and engaging for younger generations.